Netflix and Chill: An analysis of Turkish Generation Z viewers on The New Hedonistic Product - Xheni Simaku (İletişim Kuram ve Araştırma Dergisi)
In the framework of the digital attention economy, lifestyle technologies stimulate and modulate intensive participation regularly. Netflix, as a creation of the digitalization McDonald,&Smith-Rowsey (2016) with the term "the Netflix effect,” introduces a pioneering role of the platform in the streaming culture of recommendation, immediate delivery, and custom-personalized production. The algorithms and the Netflix mechanisms are designed to capitalize on the viewer's activities and to maximize the time spent on the platform; they are highly effective. With this platform, a new well-known brand was born, and with those new hedonistic consumers, the “Netflix and Chill” motto legalizes and emphasizes the brand by creating a new sort of cultural taste in a society where the emotional side of consumption is becoming more and more prominent. In this context, this paper aims to observe Turkish students' hedonistic behavior in Netflix binge-watching. A reception study will be done using focus groups; four different focus groups will be monitored. Each of these groups consisted of five Netflix viewers belonging to generation Z. The study will show the degree of viewers' hedonism and on the self-perception about it.